Full-State Feedback Control Design for Shape Formation using Linear Quadratic Regulator - Muhamad Rausyan Fikri; Djati Wibowo Djamari (Faculty of Engineering and Technology, Sampoerna University, 2020)
This study investigated the capability of a group of agents to form a desired shape formation by designing the feedback control using a linear quadratic regulator. In real application, the state condition of agents may change due to some particular problems such as a slow input response. In order to compensate for the problem that affects agent-to-agent coordination, a robust regulator was implemented into the formation algorithm. In this study, a linear quadratic regulator as the full-state feedback of robust regulator method for shape formation was considered. The result showed that a group of agents can form the desired shape (square) formation with a modification of the trajectory shape of each agent. The results were validated through numerical experiments.